The pathogenesis and therapeutic strategies of heat stroke-induced myocardial injury - Xia, Rui; Sun, Meng; Li, Yuling; Yin, Jing; Liu, Huan; Yang, Jun; Liu, Jing; He, Yanyu; Wu, Bing; Yang, Guixiang; Li, Jianhua (Frontiers in Pharmacology, 2024)
Heat stroke (HS) is a febrile illness characterized by an elevation in the core body temperature to over 40 degrees Celsius, accompanied by central nervous system impairment and subsequent multi-organ dysfunction syndrome. In recent years, the mortality rate from HS has been increasing as ambient temperatures continue to rise each year. The cardiovascular system plays an important role in the pathogenesis process of HS, as it functions as one of the key system for thermoregulation and its stability is associated with the severity of HS. Systemic inflammatory response and endothelial cell damage constitute pivotal attributes of HS, other factors such as ferroptosis, disturbances in myocardial metabolism and heat shock protein dysregulation are also involved in the damage to myocardial tissue in HS. In this review, a comprehensively detailed description of the pathogenesis of HS-induced myocardial injury is provided. The current treatment strategies and the promising therapeutic targets for HS are also discussed.